Therapeutic potentials of catalase: Mechanisms, applications, and future perspectives - Rasheed, Dr. Zafar (International Journal of Health Sciences, 2024)
Catalase, an enzyme ubiquitous in living organisms, plays a pivotal role in mitigating oxidative stress by catalyzing the decomposition of hydrogen peroxide (H2O2) into water and oxygen. Mechanistically, this action prevents the accumulation of reactive oxygen species (ROS) and consequent oxidative damage to cells and tissues. Understanding the molecular mechanisms underlying catalase activity, exploring its therapeutic applications across diverse disease contexts, addressing challenges in catalase-based therapies, and advancing novel strategies for enhanced efficacy are essential steps towards harnessing its full therapeutic potentials. In the medical realm, catalase shows promise for treating oxidative stress-related diseases such as neurodegenerative disorders, cardiovascular diseases, and inflammatory conditions. This article explores the therapeutic potentials of catalase, focusing on its mechanisms, applications, and future perspectives.